Mitral regurgitation severity assessment after percutaneous edge-to-edge mitral valve repair: guidelines-recommended integration versus volumetric assessment. (14th October 2021) - Shekel, E; Shuvy, M; Danenberg, H; Planer, D; Gilon, D; Leibowitz, D; Beeri, R
Abstract: Background: Percutaneous edge-to edge mitral valve repair (PMVr) using the MitraClip device is a common method for treating mitral regurgitation (MR) when mitral valve operation is contra-indicated or deemed too risky. The evaluation of residual MR post PMVr is crucial for understanding the benefit and prognostic effect on patients. The common methods used today, based on color flow Doppler and the appearance of the color Doppler jet, may be misguiding because of the multiple jets created by the PMVr technique. Also, flow acceleration induced by the reduced systolic orifice may exaggerate systolic flow acceleration and thus jet area. Purpose: We hypothesized that the guidelines-recommended method to assess MR may underestimate the effect of PMVr in reducing MR. Methods: Patients undergoing PMVr in a large-volume PMVr centre were recruited between 2015–2019. Post procedural MR was evaluated using the integrated qualitative approach as recommended by the guidelines. In addition, MR volume for each patient was calculated by subtracting the forward stroke volume (calculated by multiplying LVOT area with the velocity time integral of LVOT systolic flow) from the total stroke volume (using the biplane method of discs), We compared the two methods for concordance. Results: Overall, 112 cases were enrolled. In 59% of cases, the calculated volumetric residual MR was lower than the MR assessed by the integrated method. In 25.1% of patients the grade of MR was identical in both methods. In 16.2% the MR was more severe when calculated by the volumetric method (p<0.001, Kappa measure of agreement = 0.053–0.074). The reduction in residual MR degree using the volumetric approach was mostly observed in patients classified as "moderate" by the integrated qualitative approach. When considering basic characteristics and cardiac function of the patients, we did not find any sub-group of patients in whom the tendency for this mistake was higher. Conclusion: Because of multiple jet origins and clip-induced flow acceleration, the integrated method to assess MR severity, based mainly on color Doppler, is not ideal in patients after PMVr. In most cases, MR severity after MitraClip is over-estimated by the integrated, guideline-recommended integrative method when compared with a volumetric method. This is especially relevant for patients classified with "moderate" MR. This study suggests that quantitative methods, not based on colour Doppler, should be used to assess MR severity after PMVr Funding Acknowledgement: Type of funding sources: None.